Analisis Pengaruh Kualitas Pelayanan Lintas Penyeberangan Ujung – Kamal Terhadap Loyalitas Penumpang - Dewi, Riska Angga; Yenita, Yenita (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2023)
The Ujung-Kamal crossing is a crossing served by Ro-Ro ships that connects Java Island with Madura Island. In its time, the Ujung-Kamal crossing was a very busy crossing, but since the opening of the SURAMADU Bridge in June 2009, the users of Ujung-Kamal crossing services have decreased dramatically and continue to experience losses. Amid the declining number of passengers at the Ujung-Kamal crossing, this study aims to analyze the effect of service quality represented by 3 variables namely comfort, safety and reliability on passenger loyalty. This research uses quantitative descriptive method with data analysis using SEM PLS 3.0 application with data collection method using Probability Sampling method. Data analysis using SEM PLS aims to measure the relationship between variables with measuring indicators and is used to measure the causal relationship between the dependent variable and the independent variable based on the hypothesis that has been made. The results showed that comfort, safety and reliability variables affect passenger satisfaction. In addition, the safety variable is stated to have an effect on passenger loyalty but comfort and reliability are stated to have no effect on passenger loyalty. Meanwhile, if through passenger satisfaction as an intervening variable, comfort and safety affect passenger loyalty but reliability has no effect. Keywords: ferry transportation, , loyalty, satisfaction.